Functional comparison of MERS-coronavirus lineages reveals increased replicative fitness of the recombinant lineage 5 - Schroeder, Simon; Mache, Christin; Kleine-Weber, Hannah; Corman, Victor M.; Muth, Doreen; Richter, Anja; Fatykhova, Diana; Memish, Ziad A.; Stanifer, Megan L.; Boulant, Steeve; Gultom, Mitra; Dijkman, Ronald; et al. (Nature communications, 2021)
Middle East respiratory syndrome coronavirus (MERS-CoV) is enzootic in dromedary camels across the Middle East and Africa. Virus-induced pneumonia in humans results from animal contact, with a potential for limited onward transmission. Phenotypic changes have been suspected after a novel recombinant clade (lineage 5) caused large nosocomial outbreaks in Saudi Arabia and South Korea in 2016. However, there has been no functional assessment. Here we perform a comprehensive in vitro and ex vivo comparison of viruses from parental and recombinant virus lineages (lineage 3, n = 7; lineage 4, n = 8; lineage 5, n = 9 viruses) from Saudi Arabia, isolated immediately before and after the shift toward lineage 5. Replication of lineage 5 viruses is significantly increased. Transcriptional profiling finds reduced induction of immune genes IFNB1 , CCL5 , and IFNL1 in lung cells infected with lineage 5 strains. Phenotypic differences may be determined by IFN antagonism based on experiments using IFN receptor knock out and signaling inhibition. Additionally, lineage 5 is more resilient against IFN pre-treatment of Calu-3 cells (ca. 10-fold difference in replication). This phenotypic change associated with lineage 5 has remained undiscovered by viral sequence surveillance, but may be a relevant indicator of pandemic potential. MERS-CoV is enzootic in dromedary camels, can spread to humans but undergoes limited onward transmission. Here, Schroeder et al. compare clinical isolates of MERS-CoV in vitro and show that the predominantly circulating recombinant lineage 5 possess a fitness advantage over parental lineage 3 and 4 due to reduced activation of innate immune signaling.